Public Policies for Intergenerational Closing of Technological Gaps in Community Action Leaders (GEON Journal (Management, Organizations and Business), 2022)
Problematic: Based on the approach of the Technological Acceptance Model (TAM), the causes of the technological lag of community leaders are exposed, from an analysis of generational differences. Older generations are resistant to technological change. Public policies play a crucial role in closing the gap and promoting youth leadership entry into community organizations. Objectives: To analyze the consequences of the technological gap between community leaders from a TAM approach in order to issue public policies around the mitigation of generational lag. materials and methods: Description of the characteristics of dignitaries and the current and proper technological situations according to the model used. Results: There are barriers to entry and updating to technology by the older generations due to the asynchrony with the discoveries, while the new generations, who have fewer obstacles in technological acceptance, present an apolitical behavior in community leadership. Discussion: Public policies play a crucial role in closing the gap and promoting the youth participation in the management of community organizations. Conclusions: There is a technological backwardness of the dignitaries of community organizations due to generational differences marked by the low participation of young people in positions of community leadership. Contribution / originality: Finding of the main consequences of the technological backwardness of community leaders.
Keywords: community participation; digital divide; generation gap; technological change